Multiple malformations due to dysplastic changes in connective tissue in children - Protsailo, Mykhailo; Dzhyvak , Volodymyr; Krycky, Ihor; Hoshchynskyi, Pavlo; Wijaya, Andreas (Deka in Medicine, 2024)
BACKGROUND: Connective Tissue Dysplasia (CTD) in pediatric populations represents a heterogeneous group of heritable disorders characterized by structural and functional anomalies in connective tissues, primarily involving abnormalities in collagen, elastin, and other essential extracellular matrix components. These anomalies manifest through a spectrum of clinical phenotypes affecting multiple organ systems. This study aimed to investigate lesser-known systemic lesions in children with dysplastic changes in connective tissue to enable timely diagnosis and comprehensive treatment. CASE PRESENTATION: Clinical Case 1: A 15-year-old boy presented with recurrent bronchitis, pneumonia with obstructive syndrome, and asthma attacks. Allergological examination revealed significant increases in total Immunoglobulin E (IgE). Computed Tomography (CT) scans showed fibrous cortical defects and severe osteoporosis in various bones. The clinical diagnosis included undifferentiated CTD syndrome, joint hypermobility syndrome, and multiple fibrous cortical defects, among other conditions. Clinical Case 2: A 15-year-old girl with bilateral flat feet, increased thoracic kyphosis, and leftward spinal axis deviation was diagnosed with joint hypermobility syndrome. An incidental finding of a large cyst in the lower pole of the spleen was surgically treated. CONCLUSION: Dysplastic changes in connective tissue present through various clinical conditions, highlighting the need for a comprehensive examination. The combination of undifferentiated CTD with fibrous cortical defects, osteochondropathy, cystic changes in internal organs, and other developmental anomalies underscores the need for further in-depth research